Controversies in the definition and management of insignificant left-to-right shunts. Issue 3 (25th July 2013) - Cantinotti, Massimiliano; Assanta, Nadia; Murzi, Bruno; Lopez, Leo
Abstract : Haemodynamically insignificant left-to-right shunts are frequently discovered when screening for congenital heart disease, resulting in significant economic and psychosocial impact. A literature search was performed within the National Library of Medicine using the keywords small/insignificant/silent atrial septal defect (ASD), ventricular septal defect (VSD), patent ductus arteriosus (PDA) and patent foramen ovale (PFO). The search was refined by adding the keywords definition, classification and follow-up . Our analysis revealed significant heterogeneity in the evaluation and management of innocent left-to-right shunts. The definitions for small defects vary greatly, making it difficult to distinguish between physiologic and pathologic lesions (eg, a PFO vs a true ASD). Most small defects will partially or completely resolve spontaneously early in life. If spontaneous resolution does not occur, the risk for long-term complications (such as embolic events and endocarditis) is low but poses several practical and ethical issues: immediate discharge versus long-term follow-up, duration and frequency of follow-up, and content and method of discussions with the parents. Additionally, there is controversy pertaining to treatment for PDAs and VSDs, particularly among interventional cardiologists, even though risk/benefit analyses are lacking. Standards and guidelines using consensus opinion for the management of insignificant left-to-right shunts are needed to address the heterogeneity in diagnosis and management as well as use of resources, ethical and psychosocial issues.